Data resource description: National Cancer Registration Dataset in England - Henson, Katherine; Elliss-Brookes, Lucy; Coupland, Victoria; Payne, Elsita; Vernon, Sally; Rous, Brian; Rashbass, Jem (International Journal of Population Data Science, 2019)
Background The National Cancer Registration and Analysis Service (NCRAS), in Public Health England (PHE), collects and quality assures clinical information on all cases of cancer that occur in people living in England. The data collected supports the delivery of effective NHS cancer services. Aim NCRAS aims to curate a clinically rich data resource, which this abstract describes. Approach The data collected by NCRAS comes from several sources including Multi-Disciplinary Team (MDT) meetings and pathology reports. Data is reviewed by Cancer Registration Officers with the assistance of automated tools for data linkage and de-duplication of identical data sources. The data collected includes: patient identifiers; patient characteristics (e.g. sex, ethnicity); cancer specific fields (e.g. diagnosis date, cancer site, morphology, laterality, stage at diagnosis); cancer treatment fields; death information (e.g. date and cause of death); health care system information (e.g. hospital of diagnosis); and geography at diagnosis (based on patient’s postcode of residence). Results Data is submitted by 162 healthcare providers, covering over 1,700 MDTs. Population-based official statistics are available for cancers diagnosed since 1971. The data is routinely used to inform and allow evidence-based decisions about NHS service provision and patient care and to longitudinally track cancer incidence rates and survival statistics. In recent years, completeness of specific items such as stage has greatly improved. However, non-death outcomes, such as quality of life assessments and recurrence, are currently difficult to identify. Conclusion Detailed clinical information on cancer across the patient pathway enables the measurement of the diagnosis, treatment and survival outcome of all patients diagnosed with cancer. This population-based national data resource is critical to support service provision, clinical audit, commissioning, planning of services, public health and epidemiological research; all of which contribute to improved outcomes for people diagnosed with cancer.